The Relationship Of Religiosity, Producer's Knowledge, and Understanding Of Halal Products to Halal Certification - Masruroh, Nikmatul; Mahendra, M. Khoirunnas Esa (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Halal is present as a form of demand from consumers for the safety and health of the products consumed. Producers must capture the trend of this consumer behavior model as a business opportunity. So, all producers through the Law on Halal Product Guarantee No.33 of 2014, whether they understand it or not. From this, it is necessary to analyze the relationship between producer religiosity as a basis for making decisions on halal certification and the producer's knowledge and understanding regarding halal products. This study also aims to explore the relationship between religiosity, producer knowledge and understanding of halal products on certification decisions. This study uses a quantitative approach with a descriptive type. The results of this study state that if the variables of religiosity, producer knowledge and understanding of halal products are tested partially, they have no relationship with halal certification decisions by producers, but once these three variables are tested simultaneously have an impact on halal certification decisions by producers. It means that producers deciding on halal certification are not impacted by the level of religiosity, producer knowledge and understanding of halal products they have.